24‐1: Invited Paper: Flexible OLED Display Using C‐Axis‐Aligned‐Crystal/Cloud‐Aligned Composite Oxide Semiconductor Technology and Laser Separation Technology. Issue 1 (2nd June 2017) - Koezuka, Junichi; Idojiri, Satoru; Shima, Yukinori; Nakada, Masataka; Okazaki, Kenichi; Aoyama, Tomoya; Yamazaki, Shunpei
Abstract : A top‐gate self‐aligned transistor with excellent characteristics was developed using a cloud‐aligned composite oxide semiconductor (CAC‐OS). A 1058‐ppi 8K4K foldable organic light‐emitting diode panel was fabricated using the transistor and employing a novel linear laser separation technology. These technologies enable a shift of production lines from low‐temperature polysilicon to CAC‐OS.